SUBSTITUSI TEPUNG TALAS TERHADAP KUALITAS COOKIES - Lestari, Nani; Syarif, Wirnelis; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
One of an effort to reduce dependence on wheat flour in making cookies were utilizing one of the local products that can be processed is the tuber of taro as a potential source of carbohydrates which is quite high. The purpose of this study was to analyze the effect of substitution of taro flour as much as 15%, 30% and 45% of the flour used to form quality (uniform shape and the shape of the flower), brownish yellow color, smells(the fragrance and taro smells), taste (taroand sweet taste), and texture (brittleand porous texture) on cookies. The research is a pure experiment completely randomized design method using three repetitions and 30 samples. The results showed that F count > F table so that substitution of the quality of taro flour cookies effect on the quality of the form (uniform shape and form of flowers), brownish yellow color, smells (the fragrance andtaro smells), taste (sweetness and taro taste), and texture (crumbly and porous texture).Keywords: influence, substitution of taro flour, cookies quality